Book Review of Forgotten Places: Critical Studies in Rural Education - Michael Corbett (Journal of Research in Rural Education, 2018)
It is easy to begin any writing about education in rural places with the sort of corrective language that alerts the reader the dangers of rural myths and misperceptions. I will assume for the purposes of this review, that this is no longer necessary. Still, if there has ever been any doubt about the diversity of rural America, and about rural places generally, this book will put them to rest. If there is any doubt about the ways that educators and researchers engage this rural diversity, Forgotten Places adds to the existing material about strong place-sensitive rural education practice in communities challenged by multiple change forces. Finally, if there is any doubt about the range of contemporary theoretical perspectives that can (and should) be used to examine rural education, this book also provides a necessary corrective. Rural education scholarship has clearly come of age in the sense that much of it now employs sophisticated theory, engaging concepts, methodologies, ethics, and political positioning that bring the local and the global into simultaneous focus by showing how rural places have increasingly permeable boundaries, yet retain their diff erences from metropolitan geographies.